Perancangan Sistem Informasi Akuntansi Piutang Usaha Pada Bapel JPKM Surya Sumirat Menggunakan PHP MySQL - Deni Alfiansyah; S Supriyati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2020)
Receivables appear from several types of transactions, where the most common are usually due to the sale of goods or services on credit. The purpose of this study is to find how the procedure for the formation of accounts receivable that occur at the Surya Sumirat Public Health Management Corporation and designing accounting information system of accounts receivable at the Surya Sumirat Public Health Management Corporation using PHP MySQL. The Surya Sumirat Public Health Management Corporation is one of the service companies incorporated in the Borromeus Group and is engaged in the field of health insurance. The method used in this research uses two methods including descriptive research methods and survey methods, where the descriptive research methods is a research method that describes a symptom or event that is happening now while the survey method is the researcher going to the object of research to give questions to individual respondents. The problem that currently exists in the Surya Sumirat Public Health Management Corporation is the participant registration process is not by online and there is no accounting information system of account receivable. Based on these problems, the researcher hope that by proposing the design of an accounting information system for accounts receivable at the Surya Sumirat Public Health Management Corporation can overcome the current problems.